Altered fractionation radiotherapy combined with concurrent low-dose or high-dose cisplatin in head and neck cancer: A systematic review of literature and meta-analysis. (January 2018) - Szturz, Petr; Wouters, Kristien; Kiyota, Naomi; Tahara, Makoto; Prabhash, Kumar; Noronha, Vanita; Adelstein, David; Vermorken, Jan B.
Highlights: Nonsurgical treatment in advanced head & neck cancer has still unsatisfactory results. Altered fractionation chemoradiotherapy has been used as an intensification strategy. We compared concurrent three-/four-weekly high-dose versus weekly low-dose cisplatin. In this respect, high-dose single-agent cisplatin is superior to low-dose infusions. Abstract: Objectives: Altered fractionation radiotherapy and concomitant chemoradiotherapy represent commonly used intensification strategies in the management of locally advanced squamous cell carcinoma of the head and neck (LA-SCCHN). This meta-analysis compares compliance, safety, and efficacy between two single-agent cisplatin schedules given concurrently with altered fractionation radiotherapy. Methods: We systematically searched for prospective trials of patients with LA-SCCHN who received post-operative or definitive altered fractionation concurrent chemoradiotherapy. High-dose cisplatin once every three to four weeks (100 mg/m 2, 2 doses) was compared with a weekly low-dose protocol (≤50 mg/m 2, ≥4 doses). The primary outcome was overall survival. The secondary endpoints comprised treatment adherence, acute and late toxicities, and objective response rate. Results: Twelve studies with 1373 patients treated with definitive chemoradiotherapy were included. Compared to the weekly low-dose cisplatin regimen, the three- to four-weekly high-dose cisplatin regimen improved overall survival (p = .0185), was more compliant with respect to receiving all planned cycles of cisplatin (71% versus 95%, p = .0353), and demonstrated less complications in terms of severe (grade 3—4) acute mucositis and/or stomatitis (75% versus 40%, p = .0202) and constipation (8% versus 1%, p = .0066), toxic deaths (4%, versus 1%, p = .0168), 30-day mortality (8% versus 3%, p = .0154), and severe late subcutaneous fibrosis (21% versus 2%, p < .0001). Overall and complete response rates were similar between both chemotherapy schedules. Conclusion: In chemoradiotherapy incorporating altered fractionation, two cycles of high-dose cisplatin with a three to four week interval are superior to weekly low-dose schedules. Further studies should identify those who might derive the greatest benefit from this intensified approach.